Local delivery of mutant CCL2 protein‐reduced orthopaedic implant wear particle‐induced osteolysis and inflammation in vivo. Issue 1 (29th July 2015) - Jiang, Xinyi; Sato, Taishi; Yao, Zhenyu; Keeney, Michael; Pajarinen, Jukka; Lin, Tzu‐hua; Loi, Florence; Egashira, Kensuke; Goodman, Stuart; Yang, Fan
ABSTRACT: Total joint replacement (TJR) has been widely used as a standard treatment for late‐stage arthritis. One challenge for long‐term efficacy of TJR is the generation of ultra‐high molecular weight polyethylene wear particles from the implant surface that activates an inflammatory cascade which may lead to bone loss, prosthetic loosening and eventual failure of the procedure. Here, we investigate the efficacy of local administration of mutant CCL2 proteins, such as 7ND, on reducing wear particle‐induced inflammation and osteolysis in vivo using a mouse calvarial model. Mice were treated with local injection of 7ND or phosphate buffered saline (PBS) every other day for up to 14 days. Wear particle‐induced osteolysis and the effects of 7ND treatment were evaluated using micro‐CT, histology, and immunofluorescence staining. Compared with the PBS control, 7ND treatment significantly decreased wear particle‐induced osteolysis, which led to a higher bone volume fraction and bone mineral density. Furthermore, immunofluorescence staining showed 7ND treatment decreased the number of recruited inflammatory cells and osteoclasts. Together, our results support the feasibility of local delivery of 7ND for mitigating wear particle‐induced inflammation and osteolysis, which may offer a promising strategy for extending the life time of TJRs. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:58–64, 2016.